Pakistani secondary students’ learning performance and satisfaction amidst COVID-19 outbreak: Sequential explanatory research - Momna Azmat; Ayesha Ahmad (UIN Raden Mas Said Surakarta, 2022)
The COVID-19 outbreak has affected educational system and left some implications for the world of education, one of which is online learning activity. However, as a new habit of learning in post COVID-19 era nowadays, online learning should be taken as a serious consideration for conducting an effective learning environment, particularly in the context of secondary schools in Pakistan. Addressing this issue, the present study aims to explore Pakistani secondary students’ performance and satisfaction toward the practice of online learning activity in post COVID-19 era. Creswell’s Sequential explanatory research, in which qualitative data were gathered to support the finding of quantitative data, was adopted in this study. A set of questionnaires measured using five-point Likert scale and three open-ended questions were employed to collect the data from 335 secondary students in Federal Government Schools of Wah Cantt, a district in Punjab province Pakistan. The data were further analyzed using descriptive statistics by means of SPSS version 24 and thematic analysis. The results depicted that the outbreak of COVID-19 has extremely affected the students’ academic performance during the online learning activity. In terms of satisfaction, the results further demonstrated that the students possessed low level of satisfaction toward the online learning activity. Notwithstanding this fact, a strong positive correlation was proven between students’ academic performance and the level of learning satisfaction toward online learning in post COVID-19 era. Drawing on the results, this study provides implication that teachers and education stakeholders should offer dynamic and comprehensive online services, as well as supportive assistance and offensive feedback to enhance students’ performance and satisfaction toward online learning activity.